SEJARAH TARI TOPENG NATUNA DESA TANJUNG KECAMATAN BUNGURAN TIMUR LAUT KABUPATEN NATUNA - Budihardini, Sindy Sri; Tindarika, Regaria; Aditya, Mega Cantik Putri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The background of this research is there are two versions that tell about the history of Topeng Natuna Dance which is a traditional dance in Tanjung village, Bunguran Timur Laut Sub-district. This research aims to describe the history of Topeng Natuna Dance, Bunguran Timur Laut Sub-district, Natuna Regency. This research used descriptive qualitative method and it also used historical approach. The techniques of data collection used in this research is interview technique and documentation study technique. Based on the result of this study, the history of Topeng Natuna Dance is close to the first version, namely, Topeng Natuna Dance is original from Tanjung Village, Bunguran Timur Laut Sub-district, Natuna Regency. Based on the mythology, this dance existed before there was religion in society. The mask was used because a group of Topeng Natuna Dance were ashamed of being ordinary people who were invited by the King to come to his residence. This was to treat her daugher who was sick and she needed an entertaiment. Therefore, the dance group came to entertain the princess. Based on the mythology, this dance is become an entertaiment for Natuna citizen. Topeng Natuna Dance has three kinds of movements, such as, hand movement and the movement which use plate and shawl. The various movements and properties that used are an important of the historical mythology, because it is believed can help the princess to wake up from her fainting.